Development of a dual screening strategy to identify pro-angiogenic compounds from natural products: application on Tongmai Yangxin Pills. Issue 116 (15th December 2016) - Li, Lailai; Liu, Ningning; Dai, Xiangdong; Yan, Haifeng; Zhang, Ling; Xing, Leilei; Wang, Yi; Wang, Yi
Abstract : Establishment and application the dual-screening strategy to screen pro-angiogenic compounds from natural products for the first time. Abstract : Therapeutic angiogenesis was regarded as a potential treatment for ischemic diseases, and natural products are invaluable resources to identify novel compounds with pro-angiogenic activities. However, reliable and rapid strategies to identify pro-angiogenic compounds from natural products with high-throughput screening still need to be developed. We first established a dual-screening strategy by integrating a proliferation assay of human umbilical vein endothelial cells (HUVECs) in vitro with an angiogenesis assay of Tg (Fli1α:EGFP) transgenic zebra fishes in vivo to screen pro-angiogenic compounds. The active components from natural products were further identified via high performance liquid chromatography coupled with mass spectrometry. The proposed dual-screening strategy was applied to Tongmai Yangxin Pills (TMYXPs). Four active flavonoid compounds (glyasperin A, glycycoumarin, licorisoflavan A and licoisoflavone A) from TMYXPs were identified and were found for the first time to have satisfactory bioactivities for promoting HUVECs proliferation and angiogenesis in zebra fishes. Based on these results, this dual screening strategy was established to rapidly screen and identify bioactive components from natural products; this offers a novel screening assay for compounds isolated from complex natural products.